Vacancy equilibrium concentration of anharmonic crystals under pressure - Hung, Vu Van; Thanh, Do Dinh; Ha, Tran Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 12 No 4, 1996)
Abstract